2015
DOI: 10.1111/acer.12639
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Blocks Ethanol Induction of Microglial Activation and Immune Responses in the Hippocampus, Cerebellum, and Cerebral Cortex in a Mouse Model of Fetal Alcohol Spectrum Disorders

Abstract: Background Fetal alcohol spectrum disorders (FASD) result from fetal exposure to alcohol and are the leading cause of mental retardation in the United States. There is currently no effective treatment that targets the causes of these disorders. Thus, novel therapies are critically needed to limit the neurodevelopmental and neurodegenerative pathologies associated with FASD. Methods A neonatal mouse FASD model was used to examine the role of the neuroimmune system in ethanol-induced neuropathology. Neonatal C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
151
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(162 citation statements)
references
References 59 publications
9
151
2
Order By: Relevance
“…The administration of PGZ reduces ischemia-induced morphological changes in microglia of LFD-fed group, not in the HFD-fed group. This result was supported by a previous study that PGZ blocks ethanol-induced morphological changes in microglia in all brain regions that was indicative of microglial activation [48]. In this study, we also observed TNF-a and IL-1b levels in the hippocampus at 6 h after ischemia/reperfusion because these levels are peaked in the hippocampus at this time point [31].…”
Section: Discussionsupporting
confidence: 91%
“…The administration of PGZ reduces ischemia-induced morphological changes in microglia of LFD-fed group, not in the HFD-fed group. This result was supported by a previous study that PGZ blocks ethanol-induced morphological changes in microglia in all brain regions that was indicative of microglial activation [48]. In this study, we also observed TNF-a and IL-1b levels in the hippocampus at 6 h after ischemia/reperfusion because these levels are peaked in the hippocampus at this time point [31].…”
Section: Discussionsupporting
confidence: 91%
“…As an indirect estimate of microglia morphology and activation state, total cell area or “territory” (Drew et al, 2015) was measured for the cell layers of CA1, CA3, and DG using NeuroLucida software (MBF BioScience, Williston, VT). For each section, the area encompassed by an individual microglia was measured by tracing a contour from the tip of each microglial process to the next.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work has suggested alcohol-induced neuroinflammation, as measured by increased activation of microglia and levels of associated cytokines, as a potential secondary source of damage in various models of alcohol exposure, both during development and in adulthood (McClain et al, 2011; Saito et al, 2010; Kane et al, 2011; Tiwari & Chopra, 2011; Marshall et al, 2013; Drew et al, 2015; Topper et al, 2015). Alcohol exposure during the third trimester-equivalent induces waves of apoptosis in the hippocampus, possibly triggering microglial migration to the damaged tissue and activation of the resident microglia to phagocytose dying cells and debris (Miller, 1998; Ikonomidou et al, 2000; Smith et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We used a synthetic copy of the naturally-occurring 43-amino acid Tβ4 peptide (RegeneRx, Bethesda, MD, USA). The animal experiment was performed as described previously [17,18]. In brief, 4 g/kg/d ethanol or control was administered daily by intraesophageal gavage on postnatal days 4 through 9.…”
Section: Neonatal Mouse Fasd Model and Tβ4 Treatmentmentioning
confidence: 99%
“…Animals were anesthetized with isoflurane and perfused transcardially with a brief heparinized PBS flush followed by phosphate-buffered (PB) 4% paraformaldehyde fixative [18]. Double immunofluorescence was performed as previously described [12].…”
Section: Double Immunofluorescencementioning
confidence: 99%